Enhanced pharmaceutical removal from water in a three step bio-ozone-bio process. (1st July 2018) - de Wilt, Arnoud; van Gijn, Koen; Verhoek, Tom; Vergnes, Amber; Hoek, Mirit; Rijnaarts, Huub; Langenhoff, Alette
Abstract: Individual treatment processes like biological treatment or ozonation have their limitations for the removal of pharmaceuticals from secondary clarified effluents with high organic matter concentrations (i.e. 17 mg TOC/L). These limitations can be overcome by combining these two processes for a cost-effective pharmaceutical removal. A three-step biological-ozone-biological (BO3 B) treatment process was therefore designed for the enhanced pharmaceutical removal from wastewater effluent. The first biological step removed 38% of ozone scavenging TOC, thus proportionally reducing the absolute ozone input for the subsequent ozonation. Complementariness between biological and ozone treatment, i.e. targeting different pharmaceuticals, resulted in cost-effective pharmaceutical removal by the overall BO3 B process. At a low ozone dose of 0.2 g O3 /g TOC and an HRT of 1.46 h in the biological reactors, the removal of 8 out of 9 pharmaceuticals exceeded 85%, except for metoprolol (60%). Testing various ozone doses and HRTs revealed that pharmaceuticals were ineffectively removed at 0.1 g O3/g TOC and an HRT of 0.3 h. At HRTs of 0.47 and 1.46 h easily and moderately biodegradable pharmaceuticals such as caffeine, gemfibrozil, ibuprofen, naproxen and sulfamethoxazole were over 95% removed by biological treatment. The biorecalcitrant carbamazepine was completely ozonated at a dose of 0.4 g O3 /g TOC. Ozonation products are likely biodegraded in the last biological reactor as a 17% TOC removal was found. No appreciable acute toxicity towards D. magna, P. subcapitata and V. fischeri was found after exposure to the influents and effluents of the individual BO3 B reactors. The BO3 B process is estimated to increase the yearly wastewater treatment tariff per population equivalent in the Netherlands by less than 10%. Overall, the BO3 B process is a cost-effective treatment process for the removal of pharmaceuticals from secondary clarified effluents. Graphical abstract: Image 1 Highlights: A three step bio-ozone-bio process for pharmaceutical removal was investigated. Cost-effective ozonation after TOC removal in biological pre-treatment. Enhanced biodegradation of moderately biodegradable pharmaceuticals. Pharmaceutical removal will increase Dutch wastewater treatment costs by 15%. Bio-ozone-bio effluent not toxic towards D. magna, P. subcapitata and V. fischeri.